PENGEMBANGAN MEDIA PEMBELAJARAN BUDAYA RUMAH ADAT BERBASIS TRADSETIG (TRADITIONAL HOUSE TYPHOON GAME) UNTUK SISWA SEKOLAH DASAR: Media pembelajaran TRADSETIG, Budaya rumah adat, siswa sekolah Dasar - Henri; Nurhaedah, Nurhaedah; Sayidiman, Sayidiman (ETEDU : Elementary of Teacher Education, 2025)
This research was conducted in class IV of SDN No. 196 Inpres Bontomajannang on the Development of Traditional House Culture Learning Media based on Tradsetig which was motivated by the lack of learning media on traditional house culture based on games. The purpose of this study was to (1) Develop a traditional house culture learning media product based on Tradsetig for Elementary School students. (2) Determine the feasibility of the product. (3) Determine the level of practicality of using the media product. This study focuses on producing learning media to improve understanding of traditional house culture material. The design of this study is research and development (Research & Development) using the ADDIE model which consists of five stages. The first stage is: (1) Preparation. (2) Planning. (3) Development. (4) Implementation. (5) Evaluation. The conclusion of this study, based on the assessments given by material experts, media experts, teachers and students, this Tradsetig-based learning media is in the very feasible category so that it can be recommended as a learning media on traditional house culture material.